2003
DOI: 10.1183/09031936.03.00008603
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled NO and plasma cGMP increase after endotoxin infusion in healthy volunteers

Abstract: Nitric oxide (NO) is believed to be involved in the pathophysiology of sepsis. This study evaluated the activity of the NO pathway in a human endotoxin model.At baseline and after endotoxin, on-line measurements of exhaled NO (eNO) were made using a chemiluminescence technique with a single-breath method. NO-free air was inhaled prior to exhalation against a resistance. NO in orally and nasally exhaled air and in rectal gas was investigated. Plasma nitrite, nitrate, and guanosine 39, 59-monophosphate (cGMP) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
5
14
0
Order By: Relevance
“…The association between specific pneumotype and airway inflammation was evaluated utilizing eNO based on prior observations describing increased eNO in pulmonary infections and following lipopolysaccharide administration [45-47]. Our results extend these observations by demonstrating that elevated eNO may occur in association with a specific pneumotype even in the absence of overt pneumonia.…”
Section: Discussionsupporting
confidence: 72%
“…The association between specific pneumotype and airway inflammation was evaluated utilizing eNO based on prior observations describing increased eNO in pulmonary infections and following lipopolysaccharide administration [45-47]. Our results extend these observations by demonstrating that elevated eNO may occur in association with a specific pneumotype even in the absence of overt pneumonia.…”
Section: Discussionsupporting
confidence: 72%
“…In contradiction to dose-response studies in vitro [24,25], we found no effect on the inflammatory parameters by nicotinamide. In agreement with our previous studies, the endotoxin challenge evoked a marked increase in temperature, cytokines and exhaled NO [14,26]. We have previously reported data on endotoxin effect on human volunteers regarding plasma nitrite/nitrate, cGMP, platelet and leucocyte activation [14,26,27].…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our previous studies, the endotoxin challenge evoked a marked increase in temperature, cytokines and exhaled NO [14,26]. We have previously reported data on endotoxin effect on human volunteers regarding plasma nitrite/nitrate, cGMP, platelet and leucocyte activation [14,26,27]. Further, the human experimental setup with repetitive endotoxin provocations provided to be a consistent, reproducible and stable model for randomised studies.…”
Section: Discussionsupporting
confidence: 89%
“…Endotoxin (2 ng kg )1 ) elicited the expected clinical signs of an inflammatory reaction (tachycardia, fever), prominent release of cytokines studied, in agreement with previous findings in volunteers (Suffredini et al 1989, Soop et al 2003b. Endotoxin (2 ng kg )1 ) elicited the expected clinical signs of an inflammatory reaction (tachycardia, fever), prominent release of cytokines studied, in agreement with previous findings in volunteers (Suffredini et al 1989, Soop et al 2003b.…”
Section: Discussionsupporting
confidence: 91%